Analysis of The Affixation Process in The Second Victory Novel by Morris West - Chairunnisa, Tsania; Anggraeni, Dwi; Marshanda, Putri; Jumanto, Jumanto (Surakarta English and Literature Journal, 2024)
This article has explored the affixation process in the novel The Second Victory by Morris West. Affixation is a morphological process where bound morphemes or affixes are added to create diverse forms of a word. In this study, the researchers analyzed the process of affixation in the novel. This process was researched to be a source of information for readers who want to learn the process of affixation through the explanation of the base word and its affixes. This research aimed to identify the affixes and suffixes present in the novel. The researchers chose Morris West’s The Second Victory because many of Morris West’s works are set in the 40s, which makes readers feel curious about the novel. The qualitative method within analyses of existing verbal data was employed in this research. The researchers found 104 data containing 15 prefixes and 89 suffixes, with a total presentation of 100%. In this novel, the prefix that dominated was RE- which means again to indicate repetition, while the suffix that dominated was -LY which is used to form an adjective from a noun.  Using novels as a medium for learning is very effective, especially for people who like to read; therefore, the results of this study can be used to easily identify prefixes and suffixes both in terms of meaning and process in literary works.